Expression profiles of the SARS-CoV-2 host invasion genes in nasopharyngeal and oropharyngeal swabs of COVID-19 patients. Issue 10 (October 2020) - Amati, Francesca; Vancheri, Chiara; Latini, Andrea; Colona, Vito Luigi; Grelli, Sandro; D'Apice, Maria Rosaria; Balestrieri, Emanuela; Passarelli, Chiara; Minutolo, Antonella; Loddo, Sara; Di Lorenzo, Andrea; Rogliani, Paola; et al.
Abstract: We collect the nasopharyngeal and oropharyngeal swabs of 63 subjects with severe symptoms or contacts with COVID-19 confirmed cases to perform a pilot-study aimed to verify the "in situ" expression of SARS-CoV-2 host invasion genes ( ACE2, TMPRSS2, PCSK3, EMILIN1, EMILIN2, MMRN1, MMRN2, DPP4 ). ACE2 (FC = +1.88, p ≤ 0.05) and DPP4 (FC = +3, p < 0.01) genes showed a significant overexpression in COVID-19 patients. ACE2 and DPP4 expression levels had a good performance (AUC = 0.75; p < 0.001) in distinguishing COVID-19 patients from negative subjects. Interestingly, we found a significant positive association of ACE2 mRNA and PCSK3, EMILIN1, MMRN1 and MMRN2 expression and of DPP4 mRNA and EMILIN2 expression only in COVID-19 patients. Noteworthy, a subgroup of severe COVID-19 (n = 7) patients, showed significant high level of ACE2 mRNA and another subgroup of less severe COVID-19 patients (n = 6) significant raised DPP4 levels. These results indicate that a group of SARS-CoV-2 host invasion genes are functionally related in COVID-19 patients and suggests that ACE2 and DPP4 expression level could act as genomic biomarkers. Moreover, at the best of our knowledge, this is the first study that shows an elevated DPP4 expression in naso- and oropharyngeal swabs of COVID-19 patient thus suggesting a functional role of DPP4 in SARS-CoV-2 infections. Abstract : Genetics; Biochemistry; Molecular Biology; Clinical Genetics; Virology; ACE2; DPP4; SARS-CoV-2; Covid-19; Host invasion genes; Genomic Biomarkers